2019
DOI: 10.22159/ijap.2019.v11s6.33524
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Antioxidant Activity of Soursop (Annona Muricata) Leaves

Abstract: Objective: Soursop (Annona muricata) is a tropical plant which has been utilized as a folk medicine to treat many diseases including cancer, inflammation and parasitic infection. In this study, we investigated its phytochemistry properties and antioxidant activity against free radicals. Methods: Annona muricata leaves were extracted in three different solvents: ethanol, ethyl acetate and n-hexane. Afterwards, a phytochemistry test and the thin layer chromatography (TLC) method were used to evaluate bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
1
1
1
Order By: Relevance
“…In addition, the presence of alkaloids in leaves, seeds, roots and stem bark has been reported by Zine et al, (2018). However, our results differ from those of some authors such as Qorina et al, (2019) who demonstrated the presence of alkaloids and gall tannins from the extract of Annona muricata leaves using other solvents (ethanol, methanol, n-hexane and ethyl acetate). In addition, the presence of alkaloids is also noted in the methanolic extract of the leaves of Corchorus olitorius (Sadat et al, 2017).…”
Section: Qualitative Phytochemical Screeningcontrasting
confidence: 99%
“…In addition, the presence of alkaloids in leaves, seeds, roots and stem bark has been reported by Zine et al, (2018). However, our results differ from those of some authors such as Qorina et al, (2019) who demonstrated the presence of alkaloids and gall tannins from the extract of Annona muricata leaves using other solvents (ethanol, methanol, n-hexane and ethyl acetate). In addition, the presence of alkaloids is also noted in the methanolic extract of the leaves of Corchorus olitorius (Sadat et al, 2017).…”
Section: Qualitative Phytochemical Screeningcontrasting
confidence: 99%
“…The result was then compared with ascorbic acid as the positive control. The IC50 value was used as an indicator for antioxidant activity based on previous study [31,32].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Hal ini juga sesuai dengan pernyataan Hasan et al, (2020); Jannah et al, (2017); Olugbuyiro. et al, (2014); Qorina et al, (2019) bahwa ekstrak daun sirsak mengandung alkaloid, tanin, saponin, flavonoid dan fenolik. Penelitian Hasmila et al, (2019); Purnamasari et al, (2020); Usunobun et al, (2014) menunjukkan ekstrak etanol daun sirsak mengandung alkaloid, saponin, flavonoid, tanin dan fenolik.…”
Section: Skrining Fitokimiaunclassified